Comparison of the Abundance of Macrozoobenthos in Areas Affected and Unaffected by Reclamation in Pesisir Selatan District - Mufidah, Marhamah Nurul; Siregar, Sofyan Husein; Tanjung, Afrizal (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
This study aims to identify differences in macrozoobenthos abundance in areas affected and unaffected by reclamation around the Mandeh Tourism Area. This study was conducted in February–March 2023, using a survey method and sampling with the transect method. This study's results indicate that the water's condition in the Mandeh Tourism Area is still within the limits of the water quality standards and is quite good for the survival of macrozoobenthos. Macrozoobenthos found in Mandeh Tourism Area consisted of 12 families, namely Arcidae, Asterinidae, Cardiidae, Ellobiidae, Nassariidae, Neritidae, Potamididae, Siphonariidae, Trochidae, Turbinidae, Vanikoridae and Veneridae. A mixture of sand and gravel dominates the sediment type in the Mandeh Tourism Area. The total organic matter content of the sediments ranged from 3.65 to 3.90% (low). The density value of macrozoobenthos individuals in areas affected by reclamation is 5.89 ind/m2 with the highest relative density, Terebralia sulcata (26%), in areas unaffected by reclamation the average density of individuals is estimated at 10, 57 ind/m2 with abundance the highest relative is the type Pythia scarabaeus (23%).